From drifters to followers: a CIA-typology for engaging followers of scuba dive operators' Facebook pages. Issue 18 (16th September 2020) - Scholtz, Marco; Kruger, Martinette
ABSTRACT: Facebook has become a vital tool for businesses to market themselves and stand out above the competition. This is also true for the high number of dive operators that form an essential part of the marine tourism industry. Dive operators often use Facebook as a means of reaching potential clients as well as forging relationships and a sense of loyalty with their existing clients. However, little to no information is available on divers' preferences when it comes to Facebook engagement and whether different segments of the diving market resemble different preferences. The purpose of this study was therefore to develop a CIA-typology (Connection seekers, Inclusive seekers, and Attention seekers ) based on divers' preferences for social media page aspects ( dissemination, environmental information, personalisation, and distinction ) that persuade them to interact and their type of engagement ( active engagement and lurking behaviour ). This was done through an online questionnaire distributed worldwide through snowball sampling. This study revealed that Facebook followers are heterogeneous and that followers can be segmented according to their engagement preferences. This research can assist dive operators in displaying the correct messages at the most appropriate times to ensure their Facebook followers engage with their posts, thereby maximizing their marketing efforts.